2020
DOI: 10.3892/or.2020.7817
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase 3β in tumorigenesis and oncotherapy (Review)

Abstract: Glycogen synthase kinase 3β (GSK 3β), a multifunctional serine and threonine kinase, plays a critical role in a variety of cellular activities, including signaling transduction, protein and glycogen metabolism, cell proliferation, cell differentiation, and apoptosis. Therefore, aberrant regulation of GSK 3β results in a broad range of human diseases, such as tumors, diabetes, inflammation and neurodegenerative diseases. Accumulating evidence has suggested that GSK 3β is correlated with tumorigenesis and progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 142 publications
1
36
1
Order By: Relevance
“…GSK3β, a serine/threonine protein kinase, is a key enzyme involved in various diseases, including cancer ( Domoto et al, 2020 ; He et al, 2020 ). Although the role of GSK3β in cancer has been extensively studied, it still remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GSK3β, a serine/threonine protein kinase, is a key enzyme involved in various diseases, including cancer ( Domoto et al, 2020 ; He et al, 2020 ). Although the role of GSK3β in cancer has been extensively studied, it still remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Glycogen synthase kinase 3β (GSK3β) is a ubiquitously expressed serine/threonine protein kinase involved in the regulation of various cellular biological processes, including glycogen metabolism, signal transduction, cell cycle regulation, and cell proliferation ( Theeuwes et al, 2017 ). Accumulating evidence suggests that GSK3β is a crucial regulator of the oxidative stress response associated with the occurrence and development of cancer ( Domoto et al, 2020 ; He et al, 2020 ). Recent studies have shown that overexpression of GSK3β promotes erastin-induced ferroptosis and increases the sensitivity of breast cancer cells to chemotherapeutic agents ( Wu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…New bis-xanthone derivatives, secalonic acids H-M (114-119) were isolated from Penicillum oxalicum fungus (Langqi Island, Taiwan Strait). Secalonic acids H (114) and I (115) showed a weak cytotoxic effect toward HCT116, KB, and EC9706 cell lines [75], whereas compounds 116-119 exhibited moderate cytotoxicity against HeLa, HCT116, MCF-7, Hep-3B, and A549 cells. Moreover secalonic acid J (116), isolated from Penicillium oxalicum fungus, showed moderate induction of apoptosis in HeLa cells [76].…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…However, GSK 3 beta is controversial due to its bifacial roles of tumor suppression and activation. In addition, overexpression of GSK 3 beta is involved in tumor growth, and it contributes to cell sensitivity to chemotherapy [ 114 ]. Moreover, it was reported that Gsk-3 protein can be activated in SARS-CoV-2 viral infected cells which results in excessive oxidative stress via degradation of the nuclear factor erythroid 2-related factor (Nrf2) protein.…”
Section: Influence On Protein Activity and Expressionmentioning
confidence: 99%
“…This challenges the view that these transcripts play a pivotal role in the aggression elicited in stressed Tph2 +/− females [25,33] and further suggests that differences sex difference result in the differential regulation of aggression in the Tph2 +/− mice. For GSK-3β, given that the level of the phosphorylated form of this kinase is the principal determinant of its activity, activity has been shown to correlate with Gsk-3β gene expression changes [67]. However, the further assessment of the level of GSK-3β phosphorylation might be useful to -152 -confirm this association and its role in the behavioral abnormalities of Tph2 +/− females reported here.…”
Section: Previously Work Showed a Decreased Expression Of Mbp And Mag...mentioning
confidence: 69%